Therapeutic and Biodegradable Green Surfactant Kinetic Studies and Parameter Estimation with Multiple Substrates - Eswari, Jujjavarapu S. (Anti-Infective Agents, 2018)
Introduction: When environment polluted by complex petrochemical contaminants then prospective for biological treatment is needed. Methods: Biosurfactants exhibit biodegradability and anti-microbial properties hence efficacy of production and kinetics of in situ rhamnolipid production by Pseudomonas aeruginosa and lipopeptide production by Bacillus subtilis was carried out in a batch process. The need of the specific growth rate on carbon, nitrogen and phosphorous substrates was expected to monitor using Logistic, Monod, Moser and Contois type kinetic equation models. Impact of several bioprocess factors and optimization of control factors were studied. Results and Discussion: The simulation results show, Contois type model was better model than monod equation. Contois growth model says that bio mass rate depends upon the concentrations of substrate and biomass being inhibited at high concentrations of the biomass predicts, bio surfactant formation lowered with the high biomass concentration. Conclusion: The Luedeking Piret constants were calculated for rahamnolipid and lipopeptide production bearing in mind the cell survival maintenance from carbon, nitrogenand phosphorous substrates consumption. Assessed factors of this model specify that the formation of Rhamnolipid and lipopeptide was typically growth-associated.
Keywords: contois model